Assessment of land-based negative emissions options in Thailand - Norawit Suwannakarn; P. Abdul Salam (Carbon Management)
To keep the average global temperature below 1.5 °C as specified under the Paris Agreement, implementing negative emissions technologies (NETs) is imperative. This study aims to put a spotlight on negative emissions as a possible climate change mitigation option by establishing an assessment of land-based NETs in Thailand. The assessment is based on GIS analysis to identify possible lands for implementing NETs and existing factors to estimate the carbon removal potential of each technology. Different implementation scenarios are analyzed to explore the maximum implementation potential. The results show that 3% − 32% of Thailand’s areas would be available for NETs implementation depending on the land constraints of each option. Moreover, the literatures point out that Thailand is suitable for some NET options, which could increase the potential of NETs implementation. In terms of carbon removal potential, the combination of selected options could help Thailand compensate approximately 29% to 100% of the annual greenhouse gas emissions and achieve the target of Thailand’s Nationally Determined Contribution (NDC).